2019
DOI: 10.3390/toxins11020079
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation and Biological Evaluation of Maitotoxin-3, a Homologue of Gambierone, from Gambierdiscus belizeanus

Abstract: Gambierdiscus species are the producers of the marine toxins ciguatoxins and maitotoxins which cause worldwide human intoxications recognized as Ciguatera Fish Poisoning. A deep chemical investigation of a cultured strain of G. belizeanus, collected in the Caribbean Sea, led to the identification of a structural homologue of the recently described gambierone isolated from the same strain. The structure was elucidated mainly by comparison of NMR and MS data with those of gambierone and ascertained by 2D NMR dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 47 publications
7
41
0
Order By: Relevance
“…In ESI − , fragmentation of the molecular anion [M-H] − at m/z 1037.4785 showed that both molecules shared the same product ions (Table 3, Figure S2). The fragments at m/z 899.3741 [C43H63O18S]-and 96.9601 [HOSO3], which exhibited very small mass error (∆ppm < 3) in our analysis, corresponded to the two fragments also described in previous studies [5,35].…”
Section: Toxicitysupporting
confidence: 78%
See 1 more Smart Citation
“…In ESI − , fragmentation of the molecular anion [M-H] − at m/z 1037.4785 showed that both molecules shared the same product ions (Table 3, Figure S2). The fragments at m/z 899.3741 [C43H63O18S]-and 96.9601 [HOSO3], which exhibited very small mass error (∆ppm < 3) in our analysis, corresponded to the two fragments also described in previous studies [5,35].…”
Section: Toxicitysupporting
confidence: 78%
“…Studies concerning these microalgae have increased since the 1970s, after their identification as causative agents of ciguatera poisoning (CP), the most common non-bacterial intoxication affecting human consumers of seafood in the world [2]. Today, ciguatoxins (CTXs) and, to a lesser degree, maitotoxins (MTXs) are regarded as the responsible compounds for CP symptoms [3][4][5]. These toxins, as well as gambieric acids [6], gambierol [7], gambieroxide [8], and gambierones [9], are produced by the dinoflagellate genus Gambierdiscus.…”
Section: Introductionmentioning
confidence: 99%
“…Gambierone and 44-methylgambierone, which are found in high concentrations in both cells and culture medium of G. polynesiensis in the present study, are also known for their bioactive properties on cell membranes: e.g., gambierones seem to share similar biological activities with CTXs, in that they cause VGSC activation in a similar pattern as CTXs, although in much lower intensity [36]. In addition, both gambierone and 44-methylgambierone induce a small rise in the cytosolic calcium concentration in human cortical neurons, like CTXs [34], while the expression of ionotropic glutamate receptor has been shown to be modified by chronic exposure of human neurons to gambierones, an alteration that could be involved in the neurological manifestations observed in human CP [34]. Likewise, the ability of gambieric acids to bind to the site 5 of VGSCs, although with lower affinity than CTXs, has been previously described by Inoue et al (2003) [91].…”
Section: Discussionsupporting
confidence: 54%
“…In addition, two globular Gambierdiscus species have recently been reclassified as Fukuyoa yasumotoi and F. ruetzleri, with a new species described as F. paulensis [18,22,23]. These organisms are the potential source of several groups of bioactive compounds, including CTXs [24][25][26], maitotoxins (MTXs) [27][28][29], gambieric acids [30], gambierol [31,32], gambieroxide [33], and gambierones [34][35][36]. While CTXs and, to a lesser extent, MTXs have been implicated in CP [37,38], it is not fully understood if the other metabolites could also play a role in CP, but most of them are considered as compounds of interest for their bioactivity [38] and/or potential therapeutic applications [34,39].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structure of this compound was recently elucidated in two concurrent articles, after isolation from both G. australes 38 and G. belizeanus. 39 Both studies agree with MTX3 actually being 44‐methylgambierone, a congener of gambierone, another sulfated polyether compound that has recently been isolated from G. belizeanus. 40 Since the recent structural description of 44‐methylgambierone, it has also been detected in other Gambierdiscus species 41,42 …”
Section: Introductionsupporting
confidence: 67%